THE EFFECT OF HORMONES ON PHYSIOLOGICAL AND PSYCHOLOGICAL ADAPTATIONS DURING PREGNANCY - Harja, Evelyn; T, Ria Yulianti; Ai'sah; Azzahra, Akmevi Carissa; Merlinda, Euis; Fadia, Putri; Wahyuni, Rinda Tri; Dewi, Vanesa Fitriana (Universitas STRADA Indonesia, 2023)
In this study the authors raised the title of